2021
DOI: 10.1002/jev2.12053
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cell exosome delivered Zinc Finger Protein activation of cystic fibrosis transmembrane conductance regulator

Abstract: Cystic fibrosis is a genetic disorder that results in a multi-organ disease with progressive respiratory decline which leads to premature death. Mutations in the cystic fibrosis transmembrane conductance regulator (CFTR) gene disrupts the capacity of the protein to function as a channel, transporting chloride ions and bicarbonate across epithelial cell membranes. Small molecule treatments targeted at potentiating or correcting CFTR have shown clinical benefits, but are only effective for a small percentage of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 38 publications
1
21
0
Order By: Relevance
“…They replaced the chloride ions in the cells with iodide ions and incubated them with forskolin to stimulator CTFR prior to further culture in the presence of the CTFR potentiator (VX770) and corrector (VX809). In both wild type HuBECs and ∆F508 CTFR HuBECs that had been treated with CFZF-VPR exosomes, there was a significant decrease in fluorescence compared to untreated controls [71]. This confirmed the ability for MSC CFZF-VPR exosomes to be used to provide a functional repair of the CTFR mutation in HuBEC cells.…”
Section: Cystic Fibrosissupporting
confidence: 53%
See 1 more Smart Citation
“…They replaced the chloride ions in the cells with iodide ions and incubated them with forskolin to stimulator CTFR prior to further culture in the presence of the CTFR potentiator (VX770) and corrector (VX809). In both wild type HuBECs and ∆F508 CTFR HuBECs that had been treated with CFZF-VPR exosomes, there was a significant decrease in fluorescence compared to untreated controls [71]. This confirmed the ability for MSC CFZF-VPR exosomes to be used to provide a functional repair of the CTFR mutation in HuBEC cells.…”
Section: Cystic Fibrosissupporting
confidence: 53%
“…A recent study by Villamizar and colleagues was carried out to determine the potential of MS-derived exosomes for delivery of zinc finger activators targeted to the CFTR gene promoter (CFZF-VPR) [71]. Human BMMSCs (6 × 10 6 ) were co-transfected with CFZP-VPR and Connexin 43 (Cx43), and after 48 h, exosomes were harvested from the medium.…”
Section: Cystic Fibrosismentioning
confidence: 99%
“…Therefore, further exploring the mechanism of RNA and protein in exosomes is necessary. Other studies also confirmed that MSC-EXOs are feasible as a protein transport carrier [122,[125][126][127][128] (Table 4).…”
Section: Delivery Of Protein By Msc-exosmentioning
confidence: 54%
“…Furthermore, recent studies suggest that MSCs function transiently to reduce inflammation via the secretion of extra-cellular vesicles such as exosomes (Zhu et al, 2014;Zulueta et al, 2018) that can be used for delivery of drugs or gene editing material (reviewed in (Almeida-Porada et al, 2020)). Exosomes derived from MSCs genetically engineered to carry a transcription activator protein have demonstrated success in targeting and activating CFTR transcription in primary human bronchial epithelial cells from patients with CF (Villamizar et al, 2021). Further in vitro and in vivo studies are needed before this approach is considered viable.…”
Section: Identification Of Suitable Regenerative Cells With Differentmentioning
confidence: 99%